Efficacy of cavity liners with/without atmospheric cold helium plasma jet for dentin remineralization - Hamid Kermanshah; Reza Saeedi; Elham Ahmadi; Ladan Ranjbar Omrani (Medical Journals Sweden, 2020)
Aim: This study aimed to assess the efficacy of cavity liners with/without the atmospheric cold plasma jet (ACPJ) for dentin remineralization. Material and methods The occlusal third of 24 extracted third molars was cut. An occlusal cavity was prepared in the dentin of each tooth with 1 mm depth and 2 mm diameter and demineralized with 37% phosphoric acid for 1 min. The teeth were randomly divided into 8 groups (n = 3). The first control group only underwent demineralization with phosphoric acid. The second control group underwent demineralization and helium plasma jet. Groups 3 to 5 were filled with calcium hydroxide (CH), RetroMTA (MTA) and Biodentine. Groups 6 to 8 were subjected to ACPJ, and all the groups were sealed with polycarboxylate. After 2 weeks of immersion in water, the teeth were longitudinally sectioned and their mineral content was analyzed using energy-dispersive X-ray spectroscopy (EDX). Results The interaction effect of ACPJ and type of liner was not significant (p > 0.05). Application of ACPJ in combination with liner had a significant effect on calcium and phosphorous contents (p < .05). The calcium and phosphorous contents in the control groups were significantly lower than other groups (p < .05). The calcium and phosphorous contents in the CH group were higher than the control but significantly lower than the MTA and Biodentine groups. The values in the MTA and Biodentine groups were the same and higher than other groups. Conlusion All three cavity liners significantly increased the calcium and phosphorous contents of dentin. This increase was significantly greater by the MTA and Biodentine and enhanced by the ACPJ.